Regenerative stem cell therapy for stroke in Europe (RESSTORE): a multicenter randomized controlled efficacy clinical trial - Legris, Loïc; Moisan, Anaick; Jaillard, Assia; Bonnet, Louise; Moulin, Thierry; Sibon, Igor; Touzé, Emmanuel; Favre-Wiki, Isabelle; Cordonnier, Charlotte; Dellaschiava, Lucie; Mazighi, Mikael; Rosso, Charlotte; et al. (Frontiers in Stroke, 2024)
Introduction Encouraging the activation of brain repair mechanisms and fostering spontaneous functional recovery in stroke patients hold great promise for alleviating the global burden of this condition and allowing an extended therapeutic time window. Cell-based regenerative therapy (with mesenchymal stem/stromal cells, such as adipose-derived stem cells [ADSCs]) is particularly attractive considering its excellent safety profile, low immunogenicity after allogeneic application, and well-established functional benefits on stroke recovery in animal models. This study aims to assess the efficacy and safety effects of intravenous (IV) infusion of freshly cultured allogeneic ADSCs on recovery after ischemic stroke. Population and methods RESSTORE is a multicentric, randomized 1:1 controlled double-blind clinical trial. Eighty patients will be enrolled in nine French stroke centers. The main inclusion criteria are ≥18 years of age, acute hemispheric ischemic stroke, and a National Institutes of Health Stroke Scale (NIHSS) score of ≥7, including a motor subscore of ≥3. According to the previous dose-escalation safety trial data, the maximum tolerated dose of 3 million ADSCs/kg was selected. IV infusion was performed within 10 days following stroke onset, with a follow-up over 2 years. Outcomes The primary endpoint is the motor NIHSS subscore, computed as the sum of the upper limb, lower limb, and hand scores, measured 6 months after stroke onset to assess motor recovery. The secondary outcomes are the occurrence of death/serious adverse events, clinical scores (the detailed NIHSS scores, Montreal Cognitive Assessment scores, modified Rankin Scale scores, Aphasia Handicap Scores, Depression Intensity Scale Circles scores, Fatigue Scale scores, etc.), immune monitoring (for the first 30 patients), and multimodal biomarkers derived from diffusion and functional magnetic resonance imaging. Discussion This study may provide some evidence for the effects of freshly cultured allogenic ADSCs IV infusion in subacute stroke that may help design a larger international randomized controlled trial.